(Ns)QÆWA^ UKRAÇNSXKOGO SLOWA(B. (NsERÆQ LISTÆWOK DO (B85-(NRÆ^^Q Z DNQ NARODVENNQ PISXMENNIKA gEORGÆQ {EW^ENKA (B/s)E - (NwASKAN(B, (Nw(B. (Nw(B.s ((NwASILX wASILXOWI^(B)s; (NgRIGOR^UK(B-(NwOJTKO(B, (Nn(B. (Nw(B.s ((NnATAL)QÆQ wOLODIMIRÆWNA(B)s)E; (NdEM^ENKO(B, (Nw(B. (Ng(B.s ((Nw)QÆTALÆJ gRIGOROWI^(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s; (NdOWBU[(B, (No(B. )Qæ.s)E ((NoLEKSANDR )QæWANOWI^(B)s)E; (NpAN^UK(B, (Ns(B. (Nm(B.s ((NsTEPAN mIHAJLOWI^(B)s; (NpOPAD@K(B, (Nm(B. (Nm(B.s ((NmANOL)QÆJ mANOLÆJOWI^(B)s)E; (NhODOROWSXKIJ(B, (Ng(B. )Qæ.s)E ((NgEORG)QÆJ æWANOWI^(B)s)E; (NdVURAN(B, (Nw(B. (Nt(B.s ((NwASILX tODOROWI^(B)s ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2022)
(NpAM(B'(NQT)QÆ UKRAÇNSXKOGO PISXMENNIKA(B, (NVURNALÆSTA gEORGÆQ {EW^ENKA(B, (NLÆTERATURNIJ PSEWDONÆM (B"(N{EW^ENKO(B-(NgRAJ(B" (NPRISWQ^ENE DANE WIDANNQ(B. (NkOMPLEKT SKLADAÃTXSQ Z (B9-(NTI LISTÆWOK(B, (NNA KOVNÆJ Z QKIH NADRUKOWANÆ WÆR[Æ PRISWQ^ENÆ (B85-(NTÆJ RÆ^NICÆ Z DNQ NARODVENNQ PISXMENNIKA(B.s)E
(NpRO)QÃKT ~ERNÆWECXKOÇ OBLASNOÇ ORGANÆZACÆÇ nACÆONALXNOÇ SPÆLKI PISXMENNIKÆW uKRAÇNI ZA PÆDTRIMKI AWTORÆWs)E
Keywords: (N{EW^ENKO(B, (NgEORG)QÆJ pETROWI^(B,s)E -- 1937-2020 (NRR(B.s; (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E